Las tecnologías de información y comunicación (TIC) y su impacto en el sistema de compras y contrataciones públicas: el caso de la región de los lagos en Chile - Ganga Contreras, Francisco (2006)
This article underscores the impact of Information and Communication Technologies (ICTs) on organizations in the new information or knowledge society. In this effort, it addresses the main theoretical foundations of ICTs and highlights the leading role placed by the Chilean government in e-trade by creating an on-line government procurement system (ChileCompra). Additionally, it presents the results of a survey to suppliers in the Los Lagos region on their perception of this new system, in operation since 2003. Specifi cally, it aims at fi nding out what is the present status and impact of ICTs in the Los Lagos region, what are the main inconveniences suppliers fi nd in this region to operate the new system and how satisfi ed they are with these services.